Movilización social, violencia normativa y diversidades de género en México en la paradoja de los derechos humanos - Prieto Godoy, Carlos Alberto (2026)
The objective of this essay consists of identifying, from the constructivist theory of legal mobilization, the effect caused by social mobilizations occurring throughout the world to claim the rights of gender diversities in the rules of national and international law in the matter of human rights, in contrast with the social counter-mobilizations that intend to stop such a crusade. It emphasizes the regulatory violence that prevails in some federate entities of the Mexican State with regard to the recognition or refusal of the rights to the self-perceived gender identity.